AB1364 Adaptation and validation of the rheumatoid arthritis quality of life (RAQOL) scale for portugal. (12th June 2018) - Fernandes, F.; Duarte, C.; Madeira, N.; Pinto, P.; Furtado, C.; Ribeiro, C.; Couto, M.; Santos Faria, D.; Rocha, T.; Freitas, R.; Cunha, A.R.; Heaney, A.; et al.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease that has a major impact on patients' quality of life. The Rheumatoid Arthritis Quality of Life Questionnaire (RAQoL) is a patient-centric outcome measure, specific to RA. The measure has not previously been available for use with Portuguese RA patients. Objectives: To produce a Portuguese version of the RAQoL that is acceptable to Portuguese patients and demonstrates sound psychometric properties. Methods: The dual panel methodology was used to translate the UK RAQoL into Portuguese. This involved conducting a bilingual panel (providing the initial translation into Portuguese) followed by a lay panel (where items are assessed for comprehension and acceptability). Cognitive debriefing interviews were conducted with Portuguese RA patients to determine the face and content validity of the translated scale. A large-scale postal validation survey was carried out to establish the psychometric properties of the Portuguese RAQoL. The measure was administered on two occasions to RA patients, alongside a comparator instrument – the Nottingham Health Profile (NHP). Internal consistency was assessed using Cronbach's alpha coefficient. Spearman's Rank correlation coefficient was employed to assess test-retest reliability. Convergent validity was tested by correlating RAQoL scores with those on the NHP sections. Known group validity was assessed using non-parametric tests for independent samples. This involved determining the ability of the RAQoL to distinguish between patients that differed according to their self-perceived severity of RA and general health. Results: The translation panels produced a Portuguese version of the RAQoL that was easily understood and considered natural by native speakers. Interviewees considered the new language version to be relevant and appropriate. One hundred and seventy-eight RA patients (82% female) took part in the postal validation survey with a mean age of 56.6 (range 25 to 79) years. The Portuguese RAQoL demonstrated excellent internal consistency (Cronbach's α=0.95) and test-retest reliability (r=0.92), indicating that the measure produces low levels of random measurement error. RAQoL scores correlated most strongly with scores on the NHP Physical mobility scale (r=0.77) and showed moderately strong correlations with the Emotional reactions, Pain and Energy level section scores. Non-parametric tests for independent samples demonstrated significant differences in RAQoL scores between patients who differed according to their self-perceived RA severity (p<0.001) and general health (p<0.001). Conclusions: The Portuguese version of the RAQoL was found to be a comprehensive, reliable and valid questionnaire. The new language version is recommended for use in routine clinical practice and for research purposes, to assess quality of life in Portuguese RA patients. Disclosure of Interest: None declared